The hypergonadotropic hypogonadism conundrum of classic galactosemia. (13th December 2022) - Derks, Britt; Rivera-Cruz, Greysha; Hagen-Lillevik, Synneva; Vos, E Naomi; Demirbas, Didem; Lai, Kent; Treacy, Eileen P; Levy, Harvey L; Wilkins-Haug, Louise E; Rubio-Gozalbo, M Estela; Berry, Gerard T
Abstract: BACKGROUND: Hypergonadotropic hypogonadism is a burdensome complication of classic galactosemia (CG), an inborn error of galactose metabolism that invariably affects female patients. Since its recognition in 1979, data have become available regarding the clinical spectrum, and the impact on fertility. Many women have been counseled for infertility and the majority never try to conceive, yet spontaneous pregnancies can occur. Onset and mechanism of damage have not been elucidated, yet new insights at the molecular level are becoming available that might greatly benefit our understanding. Fertility preservation options have expanded, and treatments to mitigate this complication either by directly rescuing the metabolic defect or by influencing the cascade of events are being explored. OBJECTIVE AND RATIONALE: The aims are to review: the clinical picture and the need to revisit the counseling paradigm; insights into the onset and mechanism of damage at the molecular level; and current treatments to mitigate ovarian damage. SEARCH METHODS: In addition to the work on this topic by the authors, the PubMed database has been used to search for peer-reviewed articles and reviews using the following terms: 'classic galactosemia', 'gonadal damage', 'primary ovarian insufficiency', 'fertility', 'animal models' and 'fertility preservation' in combination with other keywords related to the subject area. All relevant publications until August 2022 have been critically evaluated and reviewed. OUTCOMES: A diagnosis of premature ovarian insufficiency (POI) results in a significant psychological burden with a high incidence of depression and anxiety that urges adequate counseling at an early stage, appropriate treatment and timely discussion of fertility preservation options. The cause of POI in CG is unknown, but evidence exists of dysregulation in pathways crucial for folliculogenesis such as phosphatidylinositol 3-kinase/protein kinase B, inositol pathway, mitogen-activated protein kinase, insulin-like growth factor-1 and transforming growth factor-beta signaling. Recent findings from the GalT gene-trapped ( GalT KO) mouse model suggest that early molecular changes in 1-month-old ovaries elicit an accelerated growth activation and burnout of primordial follicles, resembling the progressive ovarian failure seen in patients. Although data on safety and efficacy outcomes are still limited, ovarian tissue cryopreservation can be a fertility preservation option. Treatments to overcome the genetic defect, for example nucleic acid therapy such as mRNA or gene therapy, or that influence the cascade of events are being explored at the (pre-)clinical level. WIDER IMPLICATIONS: Elucidation of the molecular pathways underlying POI of any origin can greatly advance our insight into the pathogenesis and open new treatment avenues. Alterations in these molecular pathways might serve as markers of disease progression and efficiency of new treatment options. Graphical Abstract: